2010
DOI: 10.3109/07420528.2010.525675
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Circadian Clock and Melatonin Receptors within Cultured Rat Cardiomyocytes

Abstract: Melatonin, the pineal gland hormone, provides entrainment of many circadian rhythms to the ambient light/dark cycle. Recently, cardiovascular studies have demonstrated melatonin interactions with many physiological processes and diseases, such as hypertension and cardiopathologies. Although membrane melatonin receptors (MT1, MT2) and the transcriptional factor RORα have been reported to be expressed in the heart, there is no evidence of the cell-type expressing receptors as well as the possible role of melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…Previous studies in mammals showed that a short melatonin pulse (2 hours) is not enough to alter the expression of clock-related genes [63]. We observed that the addition of melatonin in 12-hour pulses results in oscillations in expression of N. vectensis circadian clock genes, supporting a hypothesis that the interaction of melatonin and clock genes appeared early in the evolution of the animals.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies in mammals showed that a short melatonin pulse (2 hours) is not enough to alter the expression of clock-related genes [63]. We observed that the addition of melatonin in 12-hour pulses results in oscillations in expression of N. vectensis circadian clock genes, supporting a hypothesis that the interaction of melatonin and clock genes appeared early in the evolution of the animals.…”
Section: Discussionsupporting
confidence: 82%
“…Quantitative RT-PCR was performed using specific RNA standards and TaqMan assays. Oligonucleotides sequences are reported previously (rat- Bmal1, Clock, Per1,2,3, Cry1 and Dbp (Young et al, 2001b), Slc2a4, Pdk4 and Ucp3 (Young et al, 2001a), Rora (Peliciari-Garcia et al, 2011); mice- Pdk4 and Ucp3 (Tsai et al, 2010)) or were newly designed for each gene from rat sequences available in GenBank; primer and probe sequences for newly designed assays are listed in Table 1. All quantitative RT-PCR data are presented as the number of transcripts/constitutive gene molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, functional clocks have been described in endothelia (Dermot et al, 2007;Takeda et al, 2007), adipose tissue (Zvonik et al, 2006), and fibroblasts (Welsh et al, 2004). However, rhythmic clock gene expression persists in vitro in isolated rat cardiomyocyte cultures (Durgan et al, 2005;Peliciari-Garcia, 2011), demonstrating the presence of a functional cardiomyocyte clock. Intrerestingly, exogenously administered melatonin alters circadian expression of rev-erb mRNA in rat cardiomyocyte cultures (Peliciari-Garcia et al, 2011).…”
Section: Cellular and Molecular Clocksmentioning
confidence: 99%
“…However, rhythmic clock gene expression persists in vitro in isolated rat cardiomyocyte cultures (Durgan et al, 2005;Peliciari-Garcia, 2011), demonstrating the presence of a functional cardiomyocyte clock. Intrerestingly, exogenously administered melatonin alters circadian expression of rev-erb mRNA in rat cardiomyocyte cultures (Peliciari-Garcia et al, 2011). In addition to the membrane bound melatonin receptors, RORA has been described as a functional nuclear melatonin receptor, and may provide an important link between melatonin and regulation of peripheral oscillators, including the heart (Peliciari-Garcia et al, 2011).…”
Section: Cellular and Molecular Clocksmentioning
confidence: 99%
See 1 more Smart Citation